The Role of Rural Public Libraries in Small Business Development - Bishop, Bradley Wade; Mehra, Bharat; Partee, Robert P. (Public library quarterly (New York, N.Y.), 2016)
Like all public libraries, rural public libraries in the Appalachian region can play a significant role in the economic development of their communities. Economic development in rural communities potentially benefit from many of the same resources and services all enjoy at public libraries, including free and public Internet access, space, education, question answering, and materials on many business-related subjects. This article reports survey findings of current activities that rural public libraries perform in one state, namely the state of Tennessee, as a case study to apply the lessons and insights to other parts of the United States. The discussion includes assessment of activities and some recommendations to streamline and stimulate all public libraries in conducting this assistance efficiently.